Assessment of Imaging Modalities Against Liver Biopsy in Nonalcoholic Fatty Liver Disease: The Amsterdam NAFLD‐NASH Cohort. Issue 6 (15th May 2021) - Troelstra, Marian A.; Witjes, Julia J.; van Dijk, Anne‐Marieke; Mak, Anne L.; Gurney‐Champion, Oliver; Runge, Jurgen H.; Zwirs, Diona; Stols‐Gonçalves, Daniela; Zwinderman, Aelko H.; ten Wolde, Marije; Monajemi, Houshang; Ramsoekh, Sandjai; et al.
Abstract : Background: Noninvasive diagnostic methods are urgently required in disease stratification and monitoring in nonalcoholic fatty liver disease (NAFLD). Multiparametric magnetic resonance imaging (MRI) is a promising technique to assess hepatic steatosis, inflammation, and fibrosis, potentially enabling noninvasive identification of individuals with active and advanced stages of NAFLD. Purpose: To examine the diagnostic performance of multiparametric MRI for the assessment of disease severity along the NAFLD disease spectrum with comparison to histological scores. Study Type: Prospective, cohort. Population: Thirty‐seven patients with NAFLD. Field Strength/Sequence: Multiparametric MRI at 3.0 T consisted of magnetic resonance (MR) spectroscopy (MRS) with multi‐echo stimulated‐echo acquisition mode, magnitude‐based and three‐point Dixon using a two‐dimensional multi‐echo gradient echo, MR elastography (MRE) using a generalized multishot gradient‐recalled echo sequence and intravoxel incoherent motion (IVIM) using a multislice diffusion weighted single‐shot echo‐planar sequence. Assessment: Histological steatosis grades were compared to proton density fat fraction measured by MRS (PDFFMRS ), magnitude‐based MRI (PDFFMRI‐M ), and three‐point Dixon (PDFFDixon ), as well as FibroScan® controlled attenuation parameter (CAP). Fibrosis and disease activity were compared to IVIM and MRE. FibroScan® liver stiffness measurements were compared to fibrosis levels. Diagnostic performance of all imaging parameters was determined for distinction between simple steatosis and nonalcoholic steatohepatitis (NASH). Statistical Tests: Spearman's rank test, Kruskal–Wallis test, Dunn's post‐hoc test with Holm‐Bonferroni P ‐value adjustment, receiver operating characteristic curve analysis. A P ‐value <0.05 was considered statistically significant. Results: Histological steatosis grade correlated significantly with PDFFMRS ( r s  = 0.66, P  < 0.001), PDFFMRI‐M ( r s  = 0.68, P  < 0.001), and PDFFDixon ( r s  = 0.67, P  < 0.001), whereas no correlation was found with CAP. MRE and IVIM diffusion and perfusion significantly correlated with disease activity ( r s  = 0.55, P  < 0.001, r s  = −0.40, P  = 0.016, r s  = −0.37, P  = 0.027, respectively) and fibrosis ( r s  = 0.55, P  < 0.001, r s  = −0.46, P  = 0.0051; r s  = −0.53, P  < 0.001, respectively). MRE and IVIM diffusion had the highest area‐under‐the‐curve for distinction between simple steatosis and NASH (0.79 and 0.73, respectively). Data Conclusion: Multiparametric MRI is a promising method for noninvasive, accurate, and sensitive distinction between simple hepatic steatosis and NASH, as well as for the assessment of steatosis and fibrosis severity. Level of Evidence: 2 Technical Efficacy: 2